The Potential of the Blue Economy Sector for the Development Economy in South Sulawesi - Andi Samsir; Syamsu Alam; Sri Astuti; Abd Muis (Universitas Negeri Makassar, 2023)
This research aims to find out how much is the backward linkage and forward linkage of the blue economy sector to other sectors in South Sulawesi. This research was designed with the main objective of conducting further studies and producing policy recommendations regarding the linkages between factors supporting the development of the blue economy in Indonesia in the context of food security and optimizing its role as a contributor to new sources of growth in Indonesia. Based on these research problems, this type of research is descriptive and explanatory quantitative research. The type of data used is in the form of primary and secondary data. In this study, the technique used in analyzing the data is input output analysis using the Input Output (IO) table for constant prices (17 sectors) in South Sulawesi in 2016. Based on the results of an analysis of the input-output table of South Sulawesi Province in 2016, the study indicate that the two sectors in quadrant I denote blue economic sectors. This shows that these two sectors are sectors that have good linkages to the upstream sector and the downstream sector. This means that the procurement of electricity and gas sector, and the manufacturing sector is able to both encourage and attract other sectors in increasing output in South Sulawesi.